The mass burials from the western necropolis of the Greek colony of Himera (Sicily) related to the battles of 480 and 409 BCE. (14th February 2020) - Viva, Serena; Lonoce, Norma; Vincenti, Giorgia; Cameriere, Roberto; Valentino, Matteo; Vassallo, Stefano; Fabbri, Pier Francesco
Abstract: Throughout the ancient Greek, world mass burials are rare. Of the 10, 000 excavated burials in the western necropolis of the Greek colony of Himera (649–409), only 16 contained more than one individual; seven of these can in all possibility be traced back to the two battles fought by Himera against the Carthaginians in 480 and 409 BCE. Written sources (Diod. 11.20ff.) state that the Himerans, accompanied by numerous Greek allies, defeated the Carthaginian forces in the first conflict whereas the loss of Greek allied support in the second battle resulted in the city's defeat and subsequent destruction. The anthropological and taphonomical studies of the human remains aim at testing the archaeological hypothesis that individuals interred in the seven mass graves can be related to the two battles. Skeleton density (skeletons per square metre), position, orientation, and conservation levels of the individuals in the mass burials were analysed and compared with a larger sample of 1, 000 single burials from the same necropolis along with mass graves in other forensic and archaeological contexts. Sex, age at death, presence of skeletal stress indicators, and perimortal traumas were recorded using standard anthropological methods. In the case of poorly preserved remains, sex was estimated using site‐specific discriminant functions. Although representing catastrophic samples, the results from the seven mass burials all lead to the assumption that the graves can be associated with the interment of warriors fallen in battle. Moreover, burial differences have permitted to distinguish the mass burials dating to 480 BCE from those attributed to 409 BCE.